THE ISLAMIC EDUCATIONAL VALUES IN THE PUPPETRY (Study on the story of Cungkring Takon Suwarga by Dalang Amudy Nata Prawa Cirebon West Jawa) - SA, Nurul Huda; Faridah, Lili; Nurul Huda SA (Jurnal Pendidikan Islam, 2016)
This research aims to find out: the message, the value of any Islamic education embodied in the story of Cungkring asks Suwarga and the story’s position in relation to the context of people's lives today. Research has found that there are three aspects of the message and Islamic educationa values in the story of Cungkring asks Suwarga created by puppeteer Amudy Nata Prawa. Islamic educational values that include first, the value of worship (worship to Allah), includes transcendenta worship (Ibadah Mahdhoh), the confession (Syahadat) and pray (Shalat). Secondly, social worship. Third, the universal value of education. The Position of the story of cungkring takon Suwarga and its relationship with public life today is able to become an awareness for the media and a reminder of human life after death (tadzkiratul maut) in terms of awareness about life in the hereafter. Message and Islamic educational value contained in the play Cungkring asks Suwarga can be used as a reference for parents and educators to teach Islamic education values to children. Such as education about tolerance, cooperation, honesty, modesty, loyalty, love, responsibility and so on.